Transformacja wartości a postawy przedsiębiorcze Polaków - Gruszewska, Ewa (Annales. Etyka w Życiu Gospodarczym, 2014)
Poland’s transformation occurs in individuals’ attitudes and behaviour. Several years ago, the entrepreneur in Poland was associated with corruption and border-line legal activities. Today, many entrepreneurs are looked upon as positive role models. Social acceptance of entrepreneurial attitudes in Poland is growing. Increased susceptibility to entrepreneurial behaviour in a society will increase the rate at which new businesses are established, enhancing market dynamics, and accelerating innovative changes. But in Poland entrepreneurs are not seen as a positive example, unlike in the United States. Willingness to take risks, self-expression and independence are not met with social acceptance, especially if rewarded with high incomes. The research undertaken by the author is aimed at analysing the essence of entrepreneurial attitudes and changes in the social acceptance of entrepreneurial behaviour.